Perancangan Website STMKu untuk Transparansi Pengelolaan Keuangan STM Desa Kelambir Lima Kebun - Ika Devi Perwitasari; Jodi Hendrawan; Fitri Yani Panggabean (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The establishment of the STM in Kelambir Lima Kebun Village aims to build friendship, help each other in an atmosphere of joy and sorrow among Muslims who live in Kelambir Lima Kebun Village, besides that it is also to maintain harmony in neighborly life and social relations among residents. Kelambir Lima Kebun Village in general and especially those who are Muslim. Some of the problems that then arise are financial management information that is not transparent and financial organization reports that are not yet appropriate, this can further disrupt the harmony of neighbors. Therefore, the STMKu website was created which can be a medium of information for members and the public regarding financial management information and activities carried out by the organization. The purpose of this research is to design a management system for STM financial organizations in Kelambir Lima Kebun Village. This application is built based on a website using the waterfall system development model.